2017
DOI: 10.1242/bio.026005
|View full text |Cite
|
Sign up to set email alerts
|

Bax-inhibiting peptide attenuates bleomycin-induced lung injury in mice

Abstract: Bax is a pro-apoptotic member of the Bcl-2 family of proteins, and plays a central role in mitochondria-dependent apoptosis. Several lines of evidence have implied that Bax is involved in both epithelial apoptosis and fibroblast proliferation in idiopathic pulmonary fibrosis; however, the mechanisms remain unknown. Bax-inhibiting peptide V5 (BIP-V5) exhibits membrane permeability and inhibits the activation of Bax.The purpose of this study was to investigate whether the control of Bax activity by BIP-V5 reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…For example, it has been shown that Bax expression is increased in alveolar epithelial cells of patients with IPF (Plataki et al, 2005), suggesting an involvement of MOMP in the etiology of the disease. Consistent with that, treatment with BAX-inhibiting peptide V5 (BIP-V5), which inhibits BAX activation in the cytosol, reduced inflammation and improved lung pathology and survival in a mouse model of IPF (Suzuki et al, 2017). Furthermore, deletion of Bax has been shown to extend ovarian function in aged female mice, and also resulted in significant improvements in a number of age-related phenotypes, such as increased bone mineral density and strength, better retention of lean body mass, and decreased anxiety (Perez et al, 2007).…”
Section: Therapeutic Considerations Of Cytosolic Mtdnasupporting
confidence: 63%
“…For example, it has been shown that Bax expression is increased in alveolar epithelial cells of patients with IPF (Plataki et al, 2005), suggesting an involvement of MOMP in the etiology of the disease. Consistent with that, treatment with BAX-inhibiting peptide V5 (BIP-V5), which inhibits BAX activation in the cytosol, reduced inflammation and improved lung pathology and survival in a mouse model of IPF (Suzuki et al, 2017). Furthermore, deletion of Bax has been shown to extend ovarian function in aged female mice, and also resulted in significant improvements in a number of age-related phenotypes, such as increased bone mineral density and strength, better retention of lean body mass, and decreased anxiety (Perez et al, 2007).…”
Section: Therapeutic Considerations Of Cytosolic Mtdnasupporting
confidence: 63%
“…In the early stage of apoptosis, the pro-apoptotic proteins form pores in the outer mitochondrial membrane by homologous oligomerization, resulting in cytochrome-c release and eventually caspase activation and apoptosis. 28,29 This study found that levels of the antiapoptotic protein Bcl-2 were decreased, while levels of the pro-apoptotic proteins Bax and cleaved caspase-3 were increased under oxidative stress. These results suggested that oxidative stress weakened the inhibition of apoptosis in LMSCs, while proteins that promoted apoptosis were enhanced.…”
Section: Discussionmentioning
confidence: 91%
“…50 The authors suggested that BIP may be able to block the vicious cycle of "cell death and fibrosis." 49 In this model, the temporary protection of lung epithelial cells by BIP helped stop the local inflammatory reaction against dying epithelial cells. It thus appears that Bax inhibition can mitigate the development of IPF.…”
Section: Application Of Bip For Experimental Models Of Non-neurologicmentioning
confidence: 96%
“…50 The lung fibrosis in this model is explained as the result of the local inflammatory reaction against bleomycin-induced cell death, which is caused by genotoxic stress (bleomycin is a DNA damage inducer). 50 The authors suggested that BIP may be able to block the vicious cycle of “cell death and fibrosis.” 49 In this model, the temporary protection of lung epithelial cells by BIP helped stop the local inflammatory reaction against dying epithelial cells. It thus appears that Bax inhibition can mitigate the development of IPF.…”
Section: Application Of Bip For Experimental Models Of Non-neurologicmentioning
confidence: 96%
See 1 more Smart Citation